When race and agency collide: examining pregnant black women's experiences in healthcare. Issue 3 (4th May 2022) - Wright, Kallia O.; McFarlane, Soroya Julian; Francis, Diane B.
ABSTRACT: Black women are disproportionately affected by racial disparities in maternal healthcare. Using critical race theory and the agency-identity model, this study examined how pregnant Black women communicated agency and perceived the impact of race in interactions with medical practitioners. Thirty Black women were interviewed about how they communicated with U.S. medical practitioners during pregnancy. Their responses revealed they used preemptive stereotype shields, self-agency, and information seeking on digital platforms to enhance interactions with practitioners. Also, some women argued for race-centered care and offered insights to Black mothers and to medical practitioners. Conversely, some women were uncertain about the effect of race on their care, while others wanted complete racial neutrality in their treatment. Nevertheless, this study indicates that race impacts maternal healthcare and expands understanding of stereotype threat, the sociocultural agency identity, and racial neutrality. Finally, the study may be used to support future health communication interventions regarding maternal care.